Partially exchanged organophilic bentonites - Barreto, Emerson Paes [UNESP]; Lemos, Mariana Santos; Aranha, Isabelle Bulhoes; Buechler, Pedro Mauricio [UNESP]; Dweck, Jo (Springer, 2011)
Phenol is a pollutant that has caused many problems even when present in low concentrations and still represents an environmental problem with difficult solution. This paper presents a study of phenol adsorption by organophilic clays, obtained from aVerde Claro bentonitic clay, from Bravo, Paraiba State, Brazil, at different partial cation exchange degrees with hexadecyltrimethylammonium (HDTMA) chloride, at increasing reacting ratios, from 20 to 120 mmol/100 g of clay, which were characterized in a previous paper. By using Freundlich isotherms obtained for each case, which presented the best correlation coefficients with experimental data, it can be seen that for equilibrium concentrations up to 0.53 mmol L(-1) of phenol, the adsorptive capacity decreases for organophilic bentonites obtained at cation exchange degrees higher than 80 mmol/100 g of clay. This indicates that in these cases, the higher is the exchange by organic cation, the higher is the difficulty for the phenol diffusion and sorption in the interlayer space of the organophilic clays. For higher equilibrium concentrations, the maximum adsorption occurs for the organophilic bentonite obtained at 100 mmol/100 g of bentonite exchange.
Keywords: Phenol; Organophilic clays; Partial cation exchange; Adsorption